ANALISIS PERAN UMKM DALAM MENINGKATKAN PEREKONOMIAN LOKAL DI ERA DIGITAL - Intan Lasaiva (CURVE: Journal of Economic, Business and Accounting, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital part of the Indonesian economy, contributing significantly to GDP and employment. This study aims to analyze the role of MSMEs in improving the local economy in the digital era, focusing on their contributions and the role of digital technology. The benefits include academic and practical implications for MSMEs, the government, and the community. This study uses qualitative methods that focus on the role of Micro, Small, and Medium Enterprises (MSMEs) in the local economy and the impact of digitalization on these businesses in specific regions. This study shows that MSMEs play a vital role in the local economy by significantly absorbing labor and increasing community incomes. The contribution of MSMEs to Indonesia's Gross Domestic Product (GDP) reaches more than 60%, confirming their position as the backbone of the national economy.